2015
DOI: 10.5455/ajvs.178345
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Freezability and Functional Integrity of Dromedary Camel Spermatozoa Harvested from Caput, Corpus and Cauda Epididymides

Abstract: The present study aimed to assess the freezability and functional integrity of dromedary camel spermatozoa harvested from three epididymal regions. Twenty five epididymes were obtained from slaughtered adult camels. The cauda, corpus and caput epididymides were isolated, incised and rinsed for obtaining the sperm rich fluid. Portion of this fluid was processed for cryopreservation. Fresh and frozen-thawed spermatozoa collected from different epididymal regions were evaluated for motility, livability, morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…In previous studies, with subjective evaluation of ES postthaw motility, Abdoon et al (2013) observed higher postthaw total motility (47 ± 5%) by using Ovixcell ® . By using Shotor diluent, El-Badry et al (2015) obtained total and progressive motility values of 47.4 ± 1.3% and 32.8 ± 1.3%, respectively. More recently, post-thaw CASA evaluation of ejaculated spermatozoa revealed total and progressive motility values of 38.6 ± 0.8% and 10 ± 0.7% for spermatozoa diluted with Triladyl ® (Swelum et al, 2019), andMalo et al (2019b) observed total motility values ranging from 33% to 46% and progressive motility from 8 to 18.5% for spermatozoa frozen with Green Buffer ® .…”
Section: Discussionmentioning
confidence: 97%
“…In previous studies, with subjective evaluation of ES postthaw motility, Abdoon et al (2013) observed higher postthaw total motility (47 ± 5%) by using Ovixcell ® . By using Shotor diluent, El-Badry et al (2015) obtained total and progressive motility values of 47.4 ± 1.3% and 32.8 ± 1.3%, respectively. More recently, post-thaw CASA evaluation of ejaculated spermatozoa revealed total and progressive motility values of 38.6 ± 0.8% and 10 ± 0.7% for spermatozoa diluted with Triladyl ® (Swelum et al, 2019), andMalo et al (2019b) observed total motility values ranging from 33% to 46% and progressive motility from 8 to 18.5% for spermatozoa frozen with Green Buffer ® .…”
Section: Discussionmentioning
confidence: 97%
“…The effect of seminal plasma on epididymal spermatozoa has been suggested as being due to heparin-binding proteins potentiating the ability of epididymal spermatozoa to be capacitated by heparin and to undergo acrosomal exocytosis at frequencies similar to those of epididymal sperm. Many scientists recommended the use of frozen cauda epididymal spermatozoa for mass embryo production of unknown genetic value (Katska et al, 1996;El-Badry et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Heads and tails of the epididymides were measured using a Vernier caliper. Testicular volume was calculated as: volume = [length × width × height] ×0.5236 ( 24 , 25 ).…”
Section: Methodsmentioning
confidence: 99%